2015
DOI: 10.3354/esr00625
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and dive patterns during the post-nesting migration of olive ridley turtles from French Guiana

Abstract: Behavioral plasticity allows migrating animals to adjust their migration patterns in relation to the environmental conditions they encounter during their movements. Sea turtles display long post-nesting migrations which vary considerably between species and populations. To date, there has been no description of migratory patterns of the large population of olive ridley turtles Lepidochelys olivacea in the west Atlantic. Here, we investigated dispersal and dive patterns in relation to environmental conditions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 73 publications
(136 reference statements)
4
14
0
Order By: Relevance
“…In contrast, CC tracked in our study seemed to prefer shallower waters (depth range 1-3.5 m), which aligns with depths reported for juvenile CC in the northern GoM (Lamont and Iverson, 2018). As observed in other studies (Seminoff et al, 2002;Plot et al, 2015;Christiansen et al, 2017), CM and CC displayed an apparent shift to shallower depths during the night, while no clear patterns were depicted for LK. However, contrary to typical diving patterns described for marine turtles which tend to have lower activity levels and undertake longer dives during nighttime (e.g., Mendonça, 1983;Hays et al, 2000;Schmid et al, 2002;Christiansen et al, 2017), our results suggest that for CM and CC the submergence times were longer and surfacing durations were shorter during daytime.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, CC tracked in our study seemed to prefer shallower waters (depth range 1-3.5 m), which aligns with depths reported for juvenile CC in the northern GoM (Lamont and Iverson, 2018). As observed in other studies (Seminoff et al, 2002;Plot et al, 2015;Christiansen et al, 2017), CM and CC displayed an apparent shift to shallower depths during the night, while no clear patterns were depicted for LK. However, contrary to typical diving patterns described for marine turtles which tend to have lower activity levels and undertake longer dives during nighttime (e.g., Mendonça, 1983;Hays et al, 2000;Schmid et al, 2002;Christiansen et al, 2017), our results suggest that for CM and CC the submergence times were longer and surfacing durations were shorter during daytime.…”
Section: Discussionsupporting
confidence: 88%
“…Green sea turtles nesting in French Guiana similarly used the Maroni River Estuary during their internesting period (Chambault et al, 2016) but additional occurrences are not known. In the Indian Ocean, female olive ridley turtles tagged on nesting beaches in Oman display consistent coastal use (Rees et al, 2012) but other populations of olive ridley turtles have been seen to move to offshore waters adjacent to the nesting beaches or immediately end the internesting period after their last nesting event and migrate toward foraging grounds (Whiting et al, 2007;Maxwell et al, 2011;Plot et al, 2015).…”
Section: Internesting Estuarine Movementsmentioning
confidence: 99%
“…Shallower depths in the estuary may result in reduced energy expenditure by turtles coming to the surface to breathe as they wait for egg development between clutches. During their time in the estuary, the olive ridley turtles appear to be utilizing the bottom habitat with U-shaped dives, which are likely related to resting or foraging (Figures 3, 5, Plot et al, 2015). In addition, turtles may find increased foraging opportunities in the estuary; whether olive ridley turtles forage during the internesting period is unclear, but some turtles remained in the estuary long after nesting was completed, suggesting that they were likely taking advantage of available resources, as has been hypothesized in other regions (Rees et al, 2012).…”
Section: Internesting Estuarine Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its diet consists generally of crustaceans and other invertebrates (Reichart 1993, Bjorndal 1997, and it shows a preference for foraging near estuaries and in bays with high levels of biological productivity. Several tracking studies using satellites have confirmed large offshore movements in search of feeding areas (Polovina et al 2004, Whiting et al 2007, Plotkin 2010, Plot et al 2015.…”
Section: Notes On Geographic Distributionmentioning
confidence: 99%